NEUROENDOCRINE: THE HYPOTHALAMUS-PITUITARY-ADRENAL AXIS AND THE RELATION TO STROKE - Milleniari, Rr. Fitria Dwi Intan (Universitas Pendidikan Ganesha, 2023)
Glucocorticoids are essential components to maintain homeostasis and prepare individuals to respond and manage physical and emotional stress. Cortisol, which is a glucocorticoid, is synthesized by the adrenal cortex via the hypothalamic-pituitary-adrenal axis pathway. The hypothalamus can receive external and internal environment changes signals that disrupt the organism's homeostatic balance (stressors) which then responds by releasing corticotropin-releasing hormone (CRH) and arginine vasopressin (AVP) from the paraventricular nucleus. CRH is produced through the anterior pituitary gland which then stimulates the release of adrenocorticotropic hormone (ACTH) to produce cortisol. The body's response to the stressor will have an impact on the activation of the sympathetic nervous system and have a risk relationship to stroke.